Analisis Penerapan Metode Mind Mapping Peserta Didik Pada Mata Pelajaran Geografi Di Sma Negeri Jakarta Selatan - Ersha Pangestu; Ahman Sya; Dwi Sukanti Lestariningsih (Journal on Education, 2023)
Peneli This study aims to determine the use of the mind mapping method as an instrument for assessing student learning outcomes in geography subjects at SMA Negeri Jakarta Selatan. This study uses a descriptive method with an exploratory study approach (survey). The data obtained comes from observations and open interviews with geography teachers and distributing questionnaires to students. Survey activities at schools were carried out during November-December 2022. The techniques used to analyze data were divided into 3, namely data reduction, data presentation, and data conclusion (evaluation). Based on the results of data analysis using mind mapping assessment indicators, the results obtained in SMA Negeri 60 Jakarta were 21.5 (17%) in the very high category, SMA Negeri 55 Jakarta were 17.2 (14%) in the high category, SMA Negeri 28 Jakarta was 18.4 (15%) in the high category, SMA Negeri 66 Jakarta was 17.8 (14%) in the high category, SMA Negeri 34 Jakarta was 25 (20%) in the very high category, and SMA Negeri 26 Jakarta of 25 (20%) with very high category